How would I solve the equation 25^x = 5^(4x+1)?

You would have to rewrite 25 as 5^2 hence 25^x = (5^2)^x = 5^(2*x).

Then 5^(2x) = 5^(4x+1) and therefore 2x = 4x + 1 hence 2x = -1 hence x = -1 / 2. 

Answered by Marius P. Maths tutor

7894 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find the angle between two lines with vector equations r1 = (2i+j+k)+t(3i-5j-k) and r2 = (7i+4j+k)+s(2i+j-9k)


Differentiate xcos(x) with respect to x.


Find the value of the discriminant of x2 + 6x + 11


Edexcel C1 2015 Q10. A curve with equation y = f (x) passes through the point (4, 9). Given that f′(x)=3x^(1/2)-9/(4x^(1/2))+2. Find f(x), giving each term in its simplest form.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences